Path analysis from COVID‐19 perceptions to psychological health: The roles of critical distance and mastery - Faustino, B. (2022)
Objective: The Coronavirus disease 2019 (COVID-19) pandemic was previously associated with psychopathological symptoms. However, the psychological mechanisms underlying these associations are largely unexplored. Previous studies suggested associations between metacognitive abilities (e.g., mastery) and symptomatology, which may have impacts on COVID-19 perceptions. This study aims to explore, using path analysis, the mediational role of Critical Distance (differentiation and decentration abilities) and Mastery on the relationships between COVID-19 perceptions and psychological well-being and distress. Methods: In a cross-sectional design, 227 participants (M = 34.21, SD = 10.9) filled self-report questionnaires. Results: Metacognitive abilities were negatively correlated with psychopathological symptoms. Both Critical Distance and Mastery mediated the path from COVID-19 perceived severity and anxiety to psychological distress and well-being. Critical Distance seems to augment Mastery which tends to increase psychological well-being and limited psychological distress. Conclusions: Metacognition seems to play a mediational role on the relationship between COVID-19 perceptions and mental health. Clinical psychologists and psychotherapists may enhance psychological interventions regarding COVID-19 psychopathological symptomatology by working on metacognitive Critical Distance and Mastery abilities.